Genetic polymorphism of pharmacogenomic VIP variants in the Deng people from the Himalayas in Southeast Tibet. (July 2015) - Shi, Xugang; Wang, Li; Du, Shuli; Wang, Huijuan; Feng, Tian; Jin, Tianbo; Kang, Longli
Abstract Little is known about polymorphic distribution of pharmacogenes among ethnicities, including the Deng people. In this study, we recruited 100 unrelated, healthy Deng people and genotyped them with respect to 76 different single-nucleotide polymorphisms by the PharmGKB database. Our results first indicated that the polymorphic distribution of pharmacogenes of the Deng people is most similar to CHD, suggesting that Deng people have a closest genetic relationship with CHD. Our data will enrich the database of pharmacogenomics and provide a theoretical basis for safer drug administration and individualized treatment plans, promoting the development of personalized medicine.